Rich dad's cashflow quadrant rich dad's guide to financial freedom - Kiyosaki, Robert T. (New York Warner Business Books, 2000)
Rich Dad?s CASHFLOW Quadrant is a guide to financial freedom. It?s the second book in the Rich Dad Series and reveals how some people work less, earn more, pay less in taxes, and learn to become financially free.
Keywords: Finance, Personal